2017
DOI: 10.1145/3134706
|View full text |Cite
|
Sign up to set email alerts
|

Can Biosignals be Expressive?

Abstract: We are exploring the concept of expressive biosignals: leveraging wearable technologies to introduce sensed physiological data as cues for social perception. Biosignals can help us achieve a deeper understanding of each other by revealing or clarifying the psychological processes that underlie our subjective experience. We conducted an exploratory study investigating expressive biosignals, comparing the influence of a variety of brain activity visualizations on impression formation. Results revealed that while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…Prior literature suggests the potential for expressive biosignals to affect empathy for others. In particular, several qualitative studies that deploy expressive biosignal systems (both in the wild and in laboratory settings) have demonstrated that people tend to infer and be more aware of a close contact's emotional state through displays of heart rate and skin conductance [35,38,49,51].…”
Section: Expressive Biosignals and Empathymentioning
confidence: 99%
See 4 more Smart Citations
“…Prior literature suggests the potential for expressive biosignals to affect empathy for others. In particular, several qualitative studies that deploy expressive biosignal systems (both in the wild and in laboratory settings) have demonstrated that people tend to infer and be more aware of a close contact's emotional state through displays of heart rate and skin conductance [35,38,49,51].…”
Section: Expressive Biosignals and Empathymentioning
confidence: 99%
“…Research has also shown that expressive biosignals can affect closeness with others. For instance, systems such as rings or smartwatches where you can feel or see a partner's heart rate can improve feelings of being connected with remote friends and family [49,51,56,63,69]. Janssen and colleagues demonstrate that biosignals can also increase feelings of closeness with strangers.…”
Section: Expressive Biosignals and Interpersonal Closenessmentioning
confidence: 99%
See 3 more Smart Citations